Effectiveness of First Aid Learning in Rural Areas: Local Language Short Film vs. “Toma Cemas” Module - Nastiti, Eky Madyaning; Darotin, Rida; Ekaprasetiya, Feri; Wulansari, Yunita Wahyu; Wirasakti, Guruh (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Musculoskeletal injuries in school children are one of the problems found, especially in rural areas. Providing health education on first aid for musculoskeletal injuries can build knowledge, motivation, and self-efficacy, so it is important to develop new strategies. This study analyzes the comparative effect of local language first aid short film media and the "“Toma Cemas”” module on students' knowledge, motivation, and self-efficacy. This study used a quasi-experimental method with two groups pretest-posttest. The first group received health education through local language short films and the second group received a ““Toma Cemas”” module on first aid for musculoskeletal injuries. With a population of 234 students, this study involved 84 samples divided into two groups, each consisting of 42 respondents using a stratified random sampling technique. The results of the independent t-test to assess the comparison of knowledge show p value 0.045 (p 0.05) and self–efficacy show 0.005 (p value 0.05).  There is a significant difference in the mean of knowledge and self -efficacy between the two groups there. The motivation variable shows a p value of 0.141 (p 0.05) so there is no significant difference in mean value of motivation. ““Toma Cemas”” Module is more suitable for increasing students' knowledge because the module's materials are in written form accompanied by animated images and explanations. Local language short films have a more effective influence than the ““Toma Cemas”” Module suitable for increasing students' self-efficacy related to the use of local languages, which help students feel comfortable in the process of learning first aid in rural areas.